Collagen‐Induced Arthritis Mouse Model. Issue 12 (10th December 2021) - Rosloniec, Edward F.; Whittington, Karen; Proslovsky, Amanda; Brand, David D.
Abstract: The collagen‐induced arthritis mouse model is a widely studied autoimmune model of rheumatoid arthritis. In this model, autoimmune arthritis is induced by immunization of genetically susceptible strains of mice with type II collagen emulsified in complete Freund's adjuvant. This article describes the steps necessary for the acquisition, handling, and preparation of CII, in addition to the selection of mouse strains, proper immunization technique, and methods for evaluation of the incidence and severity of the autoimmune arthritis. In this model, the first signs of arthritis appear approximately 21 to 28 days after immunization. The protocols in this article should provide the investigator with all the necessary information required to reproducibly induce a high incidence of CIA in genetically susceptible strains of mice, and to critically evaluate the pathology of the disease. Published 2021. This article is a U.S. Government work and is in the public domain in the USA. Basic Protocol : Induction of collagen‐induced arthritis Support Protocol 1 : Purification of type II collagen Support Protocol 2 : Purification of type II collagen α1(II) chains Support Protocol 3 : Assessment of arthritis incidence and severity Support Protocol 4 : Measurement of CII specific antibody by indirect ELISA Support Protocol 5 : Coupling CII to magnetic beads Support Protocol 6 : Measuring CII‐specific antibody by magnetic‐bead based ELISA Support Protocol 7 : Measurement of T cell responses to CII in CIA